Implikasi Undang-Undang No 16 Tahun 2019 Tentang Usia Pernikahan Dalam Pelaksanaan Nikah Di Bawah Umur - Hakim, Rohman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Underage marriage is only a piece of the social reality faced by today's society. Among adolescents, underage marriage is considered a way out to avoid free sex. Some do it out of necessity and because they become pregnant out of wedlock. This opinion may be true, but of course, marriage is not just uniting oneself in marriage as the answer to a problem, because the negative impact of underage marriage itself must also be considered. This also happened to the environmental community of Balongbendo District of Sidoarjo. Through an empirical juridical approach, Through an empirical juridical approach, this study aims to analyze the implications of underage marriages at KUA Balongbendo District based on Law No. 16 of 2019. The results of the study concluded: 1) The most common cause of underage marriages at KUA Balongbendo District is due to MBA (Married By Accident). 2) There has been an increase in the number of underage marriages, even though Law no. 19 of 2019 was enacted.